Blockchain for Internet of things applications: A review and open issues. (15th December 2020) - Chen, Fei; Xiao, Zhe; Cui, Laizhong; Lin, Qiuzhen; Li, Jianqiang; Yu, Shui
Abstract: Blockchain and the Internet of things (IoT) systems are attracting more and more research efforts from both academia and industry. Blockchain is rapidly evolving to be a new infrastructure for building robust distributed applications. Similarly, Internet of things is getting increasing deployment in the context of smart city, smart home, smart healthcare, etc. On the intersection of the two emerging areas, researchers are proposing to use blockchain to build more dependable IoT systems. This paper reviews the most recent research advances in this direction during the past four years. Specifically, we review, summarize, and categorize existing research works. We divide the research works into four groups according to the roles that the blockchain plays in IoT systems, i.e., access control platform, data security platform, trusted third party, and automatic payment platform. For each group, we also discuss future research challenges. From the review, we further summarize the usage paradigms and open issues on using blockchain to build dependable IoT systems. We hope this work serves as a reference of existing models for both researchers and engineers that are interested to leverage blockchain to build future IoT systems.